Behaviour of Soft Clayey Soil Improved by Fly Ash and Geogrid under Cyclic Loading - Hussein H. Karim; Zeena W. Samueel; Adel H. Jassem (Civil Engineering Journal, 2020)
The effect of Cyclic loading on the foundation behaviour of many engineering structures presents more important and related to many problems in geotechnical engineering, Especially when construction on soft ground area which represent one of the major concerns in geotechnical engineering. This paper is conducted to investigate the influence of using several improving techniques as (fly ash, Geo-grid, fly ash and Geo-grid) on the behavior of soft clayey soil subjected to cyclic loading. A total of twenty four models have been tested  which consists of a wide domain of boundary conditions, such as untreated model, Geo-grid reinforced models, fly ash treated models and models treated with fly ash incorporated with Geo-grid were conducted by varying parameters such as, footing elevations, test velocity and number of geogrid layers. The analysis demonstrates that the settlement behaviour of footing resting on treated models with fly ash and two Geo-grid layers perform better than other improving techniques.  Also observed there was an increase in settlement, which corresponds to the increase in test velocity from 6 to 9 mm/sec. Furthermore, it was conducted that the more depth of footing the soil settlement decreases. In general, when other factors remaining constant, the bearing capacity of soil goes on increasing when the depth increased.